2012
DOI: 10.1007/s12262-012-0711-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Recurrence and Complications Using Various Sclerosants by Single Dart Technique in Treatment of Ganglion Cysts

Abstract: Ganglion cysts are tense,smooth,fluctuant,cystic and transilluminant swellings. They are commonly found on the dorsum of the wrist, at the scapholunate articulation and may involve volar wrist, tendon sheaths and even inter phalangeal joints. This study aims to compare the efficacy and the recurrence rates with triamcinolone, hyaluronidase and sodium tetradecyl sulphate,using the single dart technique. This prospective observational study was conducted on patients who presented to the general surgery outpatien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(39 citation statements)
references
References 14 publications
(8 reference statements)
1
26
1
11
Order By: Relevance
“…In this study no adverse effects, including skin hypopigmentation, were observed after administration of triamcinolone [17]. This was in contrast to the aforementioned study by Chatterjee et al [10], who reported hypopigmentation in five out of 60 patients (8.3%) who were treated with triamcinolone.…”
Section: Steroidscontrasting
confidence: 94%
See 3 more Smart Citations
“…In this study no adverse effects, including skin hypopigmentation, were observed after administration of triamcinolone [17]. This was in contrast to the aforementioned study by Chatterjee et al [10], who reported hypopigmentation in five out of 60 patients (8.3%) who were treated with triamcinolone.…”
Section: Steroidscontrasting
confidence: 94%
“…In the hyaluronidase group, two patients (3.33%) developed a hypersensitivity reaction, and in one patient (1.67%) hyaluronidase administration caused skin ulceration at the injection site. Hypopigmentation of the skin was not observed in any of the patients [10].…”
Section: Chemical Substances Hyaluronidasementioning
confidence: 70%
See 2 more Smart Citations
“…Sir, We read with a lot of interest the article published in your esteemed journal titled BComparative study of recurrence and complications using various sclerosants by single dart technique in treatment of ganglion cysts^ [1]. We would like to congratulate the authors for the excellent results with minimal recurrence rate.…”
mentioning
confidence: 99%